Diversión y Juegos : Día de Campo: Comprensión de la Longitud (Fun and Games: Field Day: Understanding Length). - Berda, Chryste L. (Mathematics in the Real World Ser., 2018)
A team of students will need their measurement skills to plan their school's Field Day. This Spanish math reader builds math and literacy skills, combining problem-solving and real-world connections to help students explore math in a meaningful way.